Fintech Keuangan Syariah dalam Perspektif Konsep Syariah - Amrullah, Ata; Hasan, Asyari (Institut Agama Islam Negeri Madura, 2021)
The contextual phenomenon, sharia-based Fintech is an alternative to provide a convenience solution of the transaction process. This study wether Islamic finance fintech is in accordance with the perspective of the sharia concept or vice versa, the type of research used in this study is a literature study obtained from various sources. The specifications of this research are descriptive qualitative, namely describing the research subjects. The results show that Islamic Fintech is in accordance with the perspective of the sharia concept as evidenced by the sharia concept that must be fulfilled in transactions, namely, avoiding ribha, mayshir, tadlhis and gharar. Education related to Fintech according to the principles of sharia values ​​and concepts must target all levels of society. The development of sharia fintech is focused on the government as a regulator, higher education institutions, as well as the banking industry and other financial institutions. Fintech convenience services make people's financial needs easier to be met, as Muslims, all financial transaction processes must be based on sharia principles.